Motivation and Impact of Unregistered Marriage among the Community of Sukaramah Village, Panyipatan District, Tanah Laut Regency: Motivasi Dan Dampak Nikah Sirri Masyarakat Desa Sukaramah Kecamatan Panyipatan Kabupaten Tanah Laut - Ma’ruf Zaki Murtadho (Journal of Law, Human Rights, Immigration, and Corrections, 2025)
This study examines the motivations and social impacts of unregistered marriage (nikah sirri) among the community of Sukaramah Village, Panyipatan District, Tanah Laut Regency. Nikah sirri is a marriage conducted according to Islamic law but not officially registered with the state, resulting in no legal recognition under national marriage laws. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving community members, religious leaders, and local officials. The findings highlight key motivations including financial constraints, avoidance of bureaucratic procedures, parental disapproval, polygamous intentions, and lack of legal awareness. Despite its religious validity, nikah sirri exposes participants especially women and children to legal vulnerabilities, inheritance disputes, and limited access to public services. The study concludes nikah sirri is shaped by a complex interaction of religious beliefs, social norms, and legal understanding. It recommends enhanced community education, facilitated access to marriage registration, and stronger cooperation between religious and government institutions to reduce unregistered marriages.